Building consensus for the development of child eye care services in South Darfur State of Sudan using the Delphi technique - Saif H. Alrasheed; Kovin S. Naidoo; Peter C. Clarke-Farr; Kamal H. Binnawi (AOSIS, 2018)
Background: Global estimates suggest there are almost 19 million visually impaired children worldwide, most of whom reside in poor countries, with the major cause being treatable. Aim: To determine the barriers to accessing childhood eye care services and to develop an eye care plan for children in South Darfur State, Sudan. Setting: The study took place in South Darfur State, Sudan. Methods: The classical Delphi technique was used to build consensus on a list of statements, which were generated based on the themes established by the experts, as well as on an extensive literature review. Results: Response rates ranged from 90% in the first round (n = 18), 100% in the second round (n = 18) to 89% in the third and final round (n = 16). The total number of statements recommended by the Delphi panellists for development of the paediatric eye care plan, was 60 based on a consensus level of 80% agreement or more. The expert's consensus on the following key elements for promotion and improvement of child eye care: The main barriers to accessing child eye care were high poverty rate, unavailability of child eye services and a lack of community awareness. The challenges facing visually impaired children were an absence of paediatric ophthalmologists, low vision and orthoptic services. Conclusion: The main barriers to accessing child eye care services were financial, clinical access and lack of knowledge. There should be greater collaboration between the Ministries of Health, Education and non-governmental organisations (NGOs), to work together in addressing these barriers.